Management Of White Spot And Central Diastema On Anterior Teeth With Direct Composites Restoration (A Case Report) - Adioro Soetojo; Bintang Adiguna Widjaja (Universitas Airlangga, 2019)
Background: One of the most common aesthetic problems is discoloration and central diastema of the anterior teeth. This can make the patient's appearance disturbed and can lead to confidence in influential patients in the complex interaction of social, cultural and psychological disorders. Purpose: The purpose of this case report is to explain the management of white spot on central incisive with central diastema. Case: A 22 years old woman came to Airlangga Dental Hospital with a chief complaint of shyness and lack of confidence due to some white spot and gap on the two central front teeth. Management: The treatment of white spot and central diastema were done using a partial direct veneer technique. Conclusion: White spot and central diastema treated with partial direct veneer restoration is able to produce good aesthetic results.